2022
DOI: 10.1007/s11356-022-23954-1
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium glutamate induces cortical oxidative, apoptotic, and inflammatory challenges in rats: the potential neuroprotective role of apigenin

Abstract: Monosodium glutamate (MSG) is used as a avor, and a taste enhancer was reported to evoke marked neuronal impairments. This study investigated the neuroprotective ability of avonoid apigenin against neural damage in MSG-administered rats. Adult male rats were allocated into four groups; control, apigenin (20 mg/kg, orally), MSG (4 g/kg, orally), and apigenin + MSG at the aforementioned doses for 30 days. Regarding the levels of neurotransmitters, our results revealed that apigenin augmented the activity of acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…As mentioned earlier, stress-induced BBB permeability could account for increased access to the brain; disturbances to normal blood-brain barrier structure and function can be influenced by psychological trauma and acute and chronic stress, and may have a bidirectional relationship with mental illness (Dion-Albert et al 2022). In animal studies, MSG administration increases the burden of inflammation and oxidative stress, and lowers the amount of serotonin and gamma-aminobutyric acid (GABA) in the brain (El-Hashash et al 2023;Albrakati 2023;Ankul et al 2023). GABA is the primary inhibitory neurotransmitter in the central nervous system, and low levels have been linked to schizophrenia, major depression, and anxiety disorders (Allen et al 2023).…”
Section: Monosodium Glutamate and Neuropsychologymentioning
confidence: 99%
“…As mentioned earlier, stress-induced BBB permeability could account for increased access to the brain; disturbances to normal blood-brain barrier structure and function can be influenced by psychological trauma and acute and chronic stress, and may have a bidirectional relationship with mental illness (Dion-Albert et al 2022). In animal studies, MSG administration increases the burden of inflammation and oxidative stress, and lowers the amount of serotonin and gamma-aminobutyric acid (GABA) in the brain (El-Hashash et al 2023;Albrakati 2023;Ankul et al 2023). GABA is the primary inhibitory neurotransmitter in the central nervous system, and low levels have been linked to schizophrenia, major depression, and anxiety disorders (Allen et al 2023).…”
Section: Monosodium Glutamate and Neuropsychologymentioning
confidence: 99%
“…Interestingly, a relationship has also been seen between IL-1β and glutamate toxicity, with a decrease in glutamate toxicity when inflammation in the cerebral cortex is attenuated through elevated levels of IL-1β (69).…”
Section: Relationship Between Glutamate and The Incidence Of Anxiety ...mentioning
confidence: 99%
“…Recently, monosodium glutamate was validated using a straightforward green spectrophotometric approach, and a good correlation between the seasoning for instant noodles and Chinese salt was seen ( Elattar et al, 2023 ). Recent pieces of evidence also suggest the potential of monosodium glutamate-exposed rats to promote oxidative, apoptotic, and inflammatory challenges, which supposes the need to understand the potential risk of MSG intake among humans ( Albrakati, 2022 ). Furthermore, in ovo studies have also shown how MSG impacts fetal brain development and have revealed histological alterations in the brain, like necrosis, neuronophagia, and gliosis ( Bölükbaş and Öznurlu, 2023 ).…”
Section: Introductionmentioning
confidence: 99%